Factors Influencing Sexual Function in Postmenopausal Married Women - Hye Young Kim; Eun Ko (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study identified the level of marital intimacy, menopausal symptom and sexual function, and examined factors affecting sexual function in postmenopausal married women. METHODS: With cross-sectional survey, a sample of 245 subjects aged 45 to 60 years was recruited from January to March, 2014. Data were collected using self-reported questionnaires which included marital intimacy questionnaire (MIQ), menopause rating scale (MRS), and female sexual function index (FSFI). Data were analyzed by descriptive statistics, t-test, ANOVA, Pearson correlation coefficients and stepwise multiple regression. RESULTS: Marital intimacy, menopausal symptom and sexual function scores of subjects were 3.46±1.14, 13.71±6.61, and 12.55±8.33, respectively. Marital intimacy and menopausal symptom were related to sexual function. Variables including marital intimacy, psychosocial and urogenital menopausal symptom, period since menopause and body mass index therapy explained 51.5% in sexual function of participants. CONCLUSION: When nurses plan sexual counseling and education for sexual function of postmenopausal married women, it is necessary to consider marital intimacy, menopausal symptoms, and menopause-related factors.